Comparing governance and bargaining of livelihoods in informal settlements in Chennai and eThekwini. (June 2022) - Saharan, Tara; Pfeffer, Karin; Baud, Isa; Scott, Dianne
Abstract: Although historical developments have differently shaped urban growth trajectories of Indian and South African cities, informal settlements continue to present urgent concerns for city governments in both countries. This research explores urban governance and political bargaining of households residing in informal settlements of Chennai, India and eThekwini, South Africa across institutional and geographic scales. The article analyses two relations in a comparative framework of Chennai and eThekwini- 1) between city governments and informal settlements; and 2) livelihoods building strategy of households in relations to the informal settlements. City and settlement relations are explored by discussing the dominant planning discourses, as illustrated in policy-related documents produced by the two city governments. The article reveals that political bargaining utilising different methods forms a crucial strategy to build livelihoods. The multi-scalar analysis of households within their situated contexts reveals how their distinct trajectories of development are closely associated with the urban and settlement histories of which they are a part. The different mandates within which the settlements exist are influential in allowing households to build up their livelihoods over one or two generations. Highlights: Comparative analysis of informal settlements across geographical and institutional scales in Chennai and eThekwini. The article reveals that political bargaining utilising different methods forms a crucial strategy to build livelihoods. The research shows the influence of urban and settlement histories on development of households in informal settlements. City governments use matrices and models in planning of informal settlements as a strategy to depoliticize interventions.